2015
DOI: 10.1007/s40817-015-0003-7
|View full text |Cite
|
Sign up to set email alerts
|

The Sport Concussion Assessment Tool-Second Edition and its Relationship with Attention and Verbal Learning in a Pediatric Population

Abstract: Concussions affect over 3.8 million Americans annually, and youths comprise the majority of those affected. "Return to play" (RTP) and "return to think" (RTT) decisions following concussions are based on the assessment of several factors including symptom resolution and neuropsychological functioning. The Sport Concussion Assessment Tool-Second Edition (SCAT-2) was developed as a sideline assessment tool to aid in these decisions. Clinicians may infer neuropsychological status from results of the tool, but no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first evidence that subcomponents of the SAC-C may be important predictors of reduced neuropsychological performance 1 month after concussion. A previous study (O’Neill et al, 2015) showed that poorer SAC performance predicted more inattention and impulsivity on the CPT measure, as well as poorer verbal learning on the CVLT (measures that were also used in this study). However, participants in that study completed the SAC and neuropsychological tests concurrently, within 100 days of their concussion, rather than the acute (SAC-C) and longitudinal (neuropsychology) approach used in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…To our knowledge, this is the first evidence that subcomponents of the SAC-C may be important predictors of reduced neuropsychological performance 1 month after concussion. A previous study (O’Neill et al, 2015) showed that poorer SAC performance predicted more inattention and impulsivity on the CPT measure, as well as poorer verbal learning on the CVLT (measures that were also used in this study). However, participants in that study completed the SAC and neuropsychological tests concurrently, within 100 days of their concussion, rather than the acute (SAC-C) and longitudinal (neuropsychology) approach used in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…This test of working memory assesses performance based on backward digit span and recitation of the months of the year in reverse order. To our knowledge, only two other studies (Beauchamp et al, 2018;O'Neill et al, 2015) have focused on the predictive utility of this measure in concussion, despite its inclusion in the widely used Sports Concussion Assessment Tool (Davis et al, 2017). A previous study in the same sample found that the SAC immediate memory and concentration subtests were predictive of better neuropsychological performance at 4 and 12 weeks post-injury (Beauchamp et al, 2018).…”
Section: Discussionmentioning
confidence: 99%